1998
DOI: 10.2118/30770-pa
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and Correlation of Gas Condensate Relative Permeability by the Steady-State Method

Abstract: High-pressure core flood experiments using gas condensate fluids in long sandstone cores have been conducted. Steady-state relative permeability points were measured over a wide range of condensate-to-gas ratios (CGR; volume of condensate per unit volume of gas, both at test pressure and temperature), and the velocity and interfacial tension (IFT) were varied between tests to observe the effect on relative permeability. The experimental procedures ensured that the fluid distribution in the cores was representa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
127
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 122 publications
(139 citation statements)
references
References 9 publications
10
127
1
1
Order By: Relevance
“…Previous works including our own experimental and theoretical work (e.g., Bardon and Longeron 1980;Asar and Andy 1988;Henderson et al 1996Henderson et al , 2001 have shown that the flow behaviour at nearmiscible conditions is fundamentally different from conventional (high-IFT immiscible) gas oil flow and for the oil and gas to be considered as near-miscible the gas-oil IFT should be under 1 m Nm −1 with the effects being more pronounced with further reduction of IFT. However, at complete miscibility (IFT equal to zero), two-phase flow can no longer exist and hence flow mechanisms would be different compared to near-miscible systems.…”
Section: Fluid Systemmentioning
confidence: 82%
“…Previous works including our own experimental and theoretical work (e.g., Bardon and Longeron 1980;Asar and Andy 1988;Henderson et al 1996Henderson et al , 2001 have shown that the flow behaviour at nearmiscible conditions is fundamentally different from conventional (high-IFT immiscible) gas oil flow and for the oil and gas to be considered as near-miscible the gas-oil IFT should be under 1 m Nm −1 with the effects being more pronounced with further reduction of IFT. However, at complete miscibility (IFT equal to zero), two-phase flow can no longer exist and hence flow mechanisms would be different compared to near-miscible systems.…”
Section: Fluid Systemmentioning
confidence: 82%
“…Bardon and Longeron 1980;Asar and Handy 1988;Henderson et al 1996Henderson et al , 2001Jamiolahmady et al 2000Jamiolahmady et al , 2003 have shown that the flow behaviour at near-miscible conditions is fundamentally different from conventional (high-IFT immiscible) gas-oil flow. Jamiolahmady et al (2000Jamiolahmady et al ( , 2003 studied the flow of low IFT gas-oil systems mechanistically.…”
mentioning
confidence: 99%
“…This approach to modeling multiphase flow through porous media has been validated by numerous investigators through coreflood experiments (Chen et al, 1995;Henderson et al, 1995). For gas condensate fluids it has experimentally been shown that the mobility of both the gas and condensate phases increases with increasing capillary numbers.…”
Section: Relative Permeability Modelsmentioning
confidence: 99%
“…Gas and condensate relative permeabilities are typically determined by steady state linear coreflood experiments (Henderson et al, 1995;Whitson et al, 1999;Mott et al, 2000). Coreflood derived relative permeabilities represent rock properties of the selected core sample.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation